PENGARUH CAPITAL INTENSITY, PROFITABILITAS DAN LEVERAGE TERHADAP TAX AVOIDANCE PADA PERUSAHAAN MANUFAKTUR SEKTOR INDUSTRI BARANG KONSUMSI YANG TERDAFTAR DI BEI PERIODE 2018-2022 - Bimantoro, Harley Bayu; Sparta (Journal of Accounting, Management and Islamic Economics, 2025)
Tax avoidance is an act of tax savings that is within the scope of tax law in accordance with the law. Capital Intensity (CIR), Profitability (ROA), and Leverage (Debt Ratio) are used as independent variables in this study, which are thought to have an impact on tax avoidance (Tax Avoidance) as the dependent variable. This research will be conducted on manufacturing companies in the goods and consumption sectors that have been listed on the Indonesia Stock Exchange (IDX) for the 2018-2022 period. Company data is obtained by accessing the Indonesian Stock Exchange website. Sampling in this research used purposive sampling technique. The number of samples is 50 companies with a total of 250 observations. The data in this study were analyzed using multiple linear analysis techniques. The results of this study indicate that the Capital Intensity variable not has a negative effect on Tax Avoidance, the Profitability variable not has a negative effect on Tax Avoidance and the Leverage variable has a negative effect on Tax Avoidance.